Endoscopic third ventriculostomy: A historical review. (2nd January 2017) - Demerdash, Amin; Rocque, Brandon G.; Johnston, James; Rozzelle, Curtis J.; Yalcin, Bulent; Oskouian, Rod; Delashaw, Johnny; Tubbs, R. Shane
Abstract: Background: Endoscopic third ventriculostomy (ETV) has become one of the most common neuroendoscopic procedures. Methods: In this article, we will review the major milestones in the history of ETV development from its early use by Walter Dandy to the techniques currently employed with advanced technology. Conclusions: ETV has become an important technique in the armamentarium of the neurosurgeon. From a meager beginning with few applications, our knowledge of long-term outcomes has evolved. ETV has a rich history and more recently, has had a renewed interest in its use. Our current understanding of its indications is growing and is based on a century of development through trial and error.